Jeske van de Gevel speaks about sorghum - cowpea trials in Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Farmers in arid areas of East Africa adversely affected by climate change have an opportunity to increase their sorghum yields after research by African Biodiversity Conservation and Innovations Centre (ABCIC) and Bioversity International increases awareness and knowledge on locally adapted seeds already available in genebanks in Kenya and Tanzania. Read more: http://ow.ly/BdJ53